JUDICIAL REFORMS IN CHINA: THE WAY OF STRENGTHENING THE JUDICIAL INDEPENDENCE - Mohammad Saiful Islam; Xu Xin (Fakultas Hukum, Universitas Diponegoro, 2020)
The idea of judicial independence and Chinese courts are the parallel subject matter of discourse among the scholars in several fields in place of either judicial independence strengthen or restricted as Chinese authority continually pushes numerous judicial reform strategy year to year. The westerns, frequently, utter China’s courts are beyond enjoying appropriate independence to decide judicial verdicts solely and independently. Conversely, the Chinese leaders enunciate they entirely extempore to swallow the Western impresses as they are a cradle of rescinding the unique Chinese features. This paper, broadly, attempts to address the design of several rounds of judicial reform policy till nowadays as a means of strengthening the independence of courts. The study catches that the Chinese authority invests rigorous reform efforts to the efficient management of court administrations; to recruit better-qualified judges; to reduce internal interference from party leaders and courts seniors. They also amended laws to progress decisional independence that will extend the Chinese judiciary closer to unaffected judicial independence.